1970
DOI: 10.2307/1934049
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cs 134 in Andropogon Scoparius Michx. Clones in Two Native Habitats

Abstract: Cesium—134 distribution in native Andropogon scoparius clones and in single tillers indicates that each clone consists of a group of tillers each acting as individual plants. Two zones of concentration occur: the upper 5 cm of the roots and the inflorescence, including the florets. Cesium transport from the foliage to the upper portion of the roots occurs with fall dormancy. With the initiation of spring growth the mineral is exported from the roots to the expanding leaf blades. Cesium activity within the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…When radiophos phorus techniques were compared to the soil-block technique it was 32 found they both gave comparable results, however, the P was far less laborious (Pettit and Jaynes 1971). 14 Neilson ( 1964) used C and other radioactive materials for determining root activity_ Dodd and Van Amburg (1970) It was found that groups of tillers acted as individual plants and most of the 134Cs was concentrated in the upper 5 cm of roots.…”
mentioning
confidence: 99%
“…When radiophos phorus techniques were compared to the soil-block technique it was 32 found they both gave comparable results, however, the P was far less laborious (Pettit and Jaynes 1971). 14 Neilson ( 1964) used C and other radioactive materials for determining root activity_ Dodd and Van Amburg (1970) It was found that groups of tillers acted as individual plants and most of the 134Cs was concentrated in the upper 5 cm of roots.…”
mentioning
confidence: 99%
“…Isotopic tracers incorporated into individual ramets are not distributed throughout all ramets within the clone (Dodd andVan Amburg 1970, Colvill andMarshall 1981). Both tracer and severing experiments demonstrate that physiological integration in the caespitose graminoid S. scoparium is restricted to individual ramet sequences consisting of three connected ramet generations (Welker et al 1991b, Williams andBriske 1991, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The radionuclide 137 Cs tends to attach very strongly to many materials, especially clay minerals and organic detritus (Davis, 1963;Dodd and Van Amburg, 1970), as do many other nuclides. Radionuclides such as 3 H and 8S Kr are noteworthy exceptions in that they generally do not attach to solid objects or surfaces.…”
Section: General Conceptsmentioning
confidence: 99%